2015
DOI: 10.11628/ksppe.2015.18.2.089
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Horticulture Therapy Program Focusing on Cultivation about the Personal Relationship, Self-Esteem, and Mood of Chronic Schizophrenic Patients According to Alexithymia Levels

Abstract: The objective of this study was to feasibility search about horticultural therapy program focusing on cultivation with emotion promotion program for chronic schizophrenic patients according to alexithymia levels by analyzing effect on personal relationship, self-esteem and mood. This study was conducted once a week from March 26 th , 2014 to June 11 th , 2014 at health center in Haman for 10 chronic schizophrenic patients. Only heavy alexithymia group had significant decline about factor 1 (difficulty identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…On the other hand, in the experimental group, the total score of caregiver burden decreased from 88.30 (SD = 13.47) to 82.50 (SD = 12.16), and in the detailed item pretest-posttest score change, social activity constraints decreased from 17.50 (SD = 3.17) to 13.60 (SD = 4.43) at a significant level (p = .028). This result is similar to that of many studies proving that many subject groups showed social effects of positive change in interpersonal relations, communication and sense of closeness through horticultural therapy (Harris and Trauth, 2020;Hartig et al, 2014;Kim et al, 2019;Song et al, 2015). Such social effects of horticultural therapy appear due to interactions in the dynamic process of horticultural therapy (Relf, 1981).…”
Section: Caregiver Burdensupporting
confidence: 88%
“…On the other hand, in the experimental group, the total score of caregiver burden decreased from 88.30 (SD = 13.47) to 82.50 (SD = 12.16), and in the detailed item pretest-posttest score change, social activity constraints decreased from 17.50 (SD = 3.17) to 13.60 (SD = 4.43) at a significant level (p = .028). This result is similar to that of many studies proving that many subject groups showed social effects of positive change in interpersonal relations, communication and sense of closeness through horticultural therapy (Harris and Trauth, 2020;Hartig et al, 2014;Kim et al, 2019;Song et al, 2015). Such social effects of horticultural therapy appear due to interactions in the dynamic process of horticultural therapy (Relf, 1981).…”
Section: Caregiver Burdensupporting
confidence: 88%